Implementasi Metode Bernyanyi dalam Pembelajaran Anak Usia Dini: Pelafalan Rukun Islam di TK Terpadu Buah Hati Cerdas - Iin Septianingsih; Ld Abdul Salam Al Amin; Lusi Sonia Pratiwi; Delia Saida; Ayu Sitriani (Institut Nalanda, 2025)
This study aims to explore the effectiveness of the singing method in teaching the pillars of Islam to early childhood children in early childhood education (PAUD). The study used classroom action research with a descriptive qualitative approach. The subjects were children in Group B2 of the Buah Hati Cerdas Integrated Kindergarten, using observation, interviews, and documentation as instruments. The results showed that the singing method improved children's pronunciation of the pillars of Islam, expanded vocabulary, and strengthened articulation. Furthermore, this method created an interactive and collaborative classroom atmosphere, enhancing children's motivation, self-confidence, and social-emotional skills. Learning effectiveness was further enhanced when the singing method was combined with multimodal approaches, such as movement, visuals, and simple games. The successful implementation of this method depended heavily on the teacher's creativity in selecting, adapting, and linking songs to the learning content. This study concluded that the singing method is an innovative strategy in early childhood Islamic education because it supports not only cognitive aspects but also character development and religiosity from an early age.